Usulan Pengembangan Komunikasi Pemasaran Melalui Strategi Customer Bonding (Studi Kasus : Supermarket Hero di Jakarta) - Sukwadi, Ronald (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2007)
The consequence of competition is the decrease of the number of customers which causes Hero Supermarket closed down several of its outlets. This decrease is also caused by the existence of internal issue of marketing communication (promotion) which lacked a strong concept. The ineffective selection of communication channel which in turn fails to conform the activity to the public. For that, the identification in marketing communication activity through Customer Bonding strategy is needed. Through marketing communication program assessment with Customer Bonding (Awareness Bonding, Relationship Bonding, and Advocacy Bonding), intensity of marketing communication problem can be identified, through survey assessment (management and costumer), analyzed with statistical testing like validity and reliability test, Spearman Correlation test and Cross tab test. The questionnaires will be given to 13 respondents from Hero Management by using quota sampling and 100 customers using stratified sampling. Through marketing communication program assessment using Customer Bonding, marketing communication intensity and correlation analysis between marketing communication program and consumer loyalty are obtained. From this analysis, it is shown that there is noise in marketing communication that influences information sending to customer. Hero must maintain marketing communication program which focuses in marketing program that have competitive advantages. Beside that, evaluation has always to be done in order to improve customer loyalty. Keywords: communication, customer bonding, loyalty